A Review on Polymeric Nanoparticles: A Promising Novel Drug Delivery System - Anup Naha (Journal of Global Pharma Technology, 2018)
Polymeric nanoparticles[PNPs] has been considered as a promising drug delivery system for a variety of drugs, anticancer agents, biological macromolecules and vaccines.These nanoparticles are a novel approach and plausible solution for conventional therapeutics, prophylactic and diagnostic options. Polymeric nanoparticles (PNPs) are Nano sized solid particles orparticulate dispersions with size ranging from10nm to 1000nm. With its enormous potential PNPs offers vast scope for researches in this field. This article covers properties of polymeric nanoparticles, its therapeutic applications, polymers used in preparation, method of preparation and characterization.Keywords: Polymeric nanoparticles (PNPs), Polymerization, Drug delivery system.